Economic Impacts of the Turfgrass and Lawncare Industry in the United States - John J. Haydu; Alan W. Hodges; Charles R. Hall (EDIS)
The turfgrass and lawncare industry in the United States continues to grow rapidly due to strong demand for residential and commercial property development, rising affluence, and the environmental and aesthetic benefits of turfgrass in the urban landscape. Economic sectors of the industry include sod farms, lawncare services, lawn and garden retail stores, and lawn equipment manufacturing. Golf courses were also included in this study as a major industry that depends upon highly managed turfgrass for golf play. Numerous studies have been conducted on the economic impacts of the turfgrass and lawncare industry for individual states or regions; however, this research is the first to report results for the entire United States. This is EDIS document FE632, a publication of the Food and Resource Economics Department,  UF/IFAS Extension. Published April 2006.